2018
DOI: 10.1093/mnras/sty2720
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray quasi-periodicities of blazars. A cautious approach

Abstract: The availability of about a decade of uninterrupted sky monitoring by the Fermi satellite has made possible to study long-term quasi-periodicities for high-energy sources. It is therefore not a surprise that for several blazars in the recent literature claims for such periodicities, with various level of confidence, have been reported. The confirmation of these findings could be of tremendous importance for the physical description of this category of sources and have consequences for the gravitational wave ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 45 publications
(60 reference statements)
7
63
0
Order By: Relevance
“…The results are shown in Table. 8 and reveal that in the absence of other physical reasons for restricting the period range the QPV evidence is strongly reduced, with none of the sources reaching 3σ significance. These findings are in line with similar indications in (Covino et al 2019).…”
Section: Global Significancesupporting
confidence: 93%
“…The results are shown in Table. 8 and reveal that in the absence of other physical reasons for restricting the period range the QPV evidence is strongly reduced, with none of the sources reaching 3σ significance. These findings are in line with similar indications in (Covino et al 2019).…”
Section: Global Significancesupporting
confidence: 93%
“…Ackermann et al 2015;Prokhorov & Moraghan 2017;Ait Benkhali et al 2019), there are other studies which demonstrate that there is no solid evidence supporting such hints of year-long periodicities in blazars (e.g. Covino et al 2019). We emphasise that caution is required when claiming quasi-periodicities on timescales of a few years in blazar γ-ray emission.…”
Section: Discussionmentioning
confidence: 73%
“…It is important to note here that in all of these cases the claimed periodic timescales were nearly two years and above (or low temporal frequency), and number of observed periodic cycles were less than 5. More recently, Covino et al (2019) studying several blazars in γ-ray reported no significant periodicities in the light curves.…”
Section: Introductionmentioning
confidence: 97%